Targeting the EphB4 receptor tyrosine kinase sensitizes HER2-positive breast cancer cells to Lapatinib. (10th April 2020) - Ding, Jinlei; Yao, Yating; Huang, Gena; Wang, Xiaonan; Yi, Jingyan; Zhang, Nan; Liu, Chongya; Wang, Kainan; Zhang, Yuan; Wang, Min; Liu, Pixu; Ye, Mingliang; et al.
Abstract: Clinical data analysis reveals that the expression of the EphB4 receptor tyrosine kinase is significantly elevated in HER2-positive breast cancer and high levels of EphB4 strongly correlate with poor disease prognosis. However, the impact of EphB4 activation on HER2-positive breast cancer cells and the potential of EphB4 as a therapeutic target remain to be explored. Here, we show that EphB4 overexpression confers gain-of-function activities to HER2-positive breast cancer cells, rendering resistance to a HER2/EGFR inhibitor Lapatinib. Furthermore, using integrated transcriptomic and tyrosine phosphoproteomic analyses, followed by biochemical confirmation, we establish that EphB4 activation engages the SHP2/GAB1-MEK signaling cascade and downstream c-MYC activation, and thereby limits the overall drug responses to Lapatinib. Finally, we demonstrate that, in HER2-positive breast tumors, inhibition of EphB4 combined with Lapatinib is more effective than either alone. These findings provide new insights into the signaling networks dictating therapeutic response to Lapatinib as well as a rationale for co-targeting EphB4 in HER2-positive breast cancer. Highlights: High levels of EphB4 correlate with poor prognosis in HER2-positive breast cancer. EphB4 activation confers resistance to Lapatinib. EphB4 activation engages the SHP2/GAB1/MEK/MYC signaling axis. Inhibition of EphB4 sensitizes HER2-positive breast tumors to Lapatinib.